Systematic Literature Review: Sustainable Framework of the Employee Green Behavior Research Agenda - Yanhong Xu; Nor Azma Rahlin; Sharifah Rahama Amirul (Journal of Propulsion Technology, 2024)
This study aims to provide insightful knowledge on key concepts in employee green behavior, identify factors influencing employee green behavior, and examine the most common theories in the study of employee green behavior. The researchers used the Scopus database and Google Scholar platform to search and cite 88 relevant literature sources using the keywords "employee green behaviour, employee pro-environment behaviour, and green human resources" for this review. A PRISMA systematic literature review primarily examines full-text articles published between 1958 and 2023 that discuss employee green behaviour. The results of this study indicated that factors influencing green behaviour can be divided into two levels: the individual level and the organizational level. This study revealed that several factors influence green behaviour at the individual level, such as personality traits, green motivation, perception, value, and attitude. On the other hand, the factors influencing green behavior at the organizational level are leadership, organizational climate, management practices, and corporate responsibility. In addition, several theories have been frequently utilized in green behavior studies, including the theories of planned behavior, self-determination, social exchange, and social learning. Finally, this study presents the limitations of this systematic literature review and makes recommendations for future research.